Digital Transformation of Islamic Education: An Artificial Intelligence-Based Teaching Module Development Study - Zuhriyeh, Siti; Ali, Moh; Hidayat, Ade (research, training and philanthropy institution Natural Aceh, 2025)
This research examines digital transformation in Islamic Religious Education through the development of AI-based teaching modules. Using a qualitative approach with library research design, the study analyzes the concept and implementation of digital transformation in Islamic education, designs an AI-based teaching module development model, and evaluates its implications for learning processes and outcomes. The findings reveal three foundations of digital transformation in Islamic education: technology-spirituality synergy, moderation principles in technological adoption, and contextualizing religious materials in the digital landscape. The development of AI-based Islamic education teaching modules involves five essential components contributing to enhanced religious digital literacy, learning motivation, higher-order thinking skills, and democratization of access to Islamic knowledge. Research implications emphasize the importance of a balance between technological innovation and the preservation of fundamental Islamic educational values in optimizing the digital transformation of religious education in the contemporary era.